Influence of the reasonable crack initiation force obtained by coupling AE parameters and stress-strain on low-stress cropping quality. (July 2022) - Xu, Jiayi; Zhang, Dexiao; Zhou, Qiang; Sun, Xudong; Yang, Ning; Guo, Weijian; Fu, Shulin; Zhang, Lijun
In view of the problem that it is difficult to accurately obtain the crack initiation force required for the metal bar with V-shaped notch in the low-stress precision cropping, a new method for synchronous measurement of coupling AE parameters and stress–strain is proposed, and a corresponding test platform is also established. By analyzing the ringing count and RMS parameters of AE, it is found that the crack at the tip of V-shaped notch begins to appear at the boundary between the crack accumulation area and the plastic failure area. At the moment, the reasonable crack initiation force for metal bar with V-shaped notch can also be determined by coupling the value of strain. Based on it, a new constant loading curve based on the F R is built. The results show that by means of the constant loading curve, the crack initiation time and the area of bar transient breaking zone are reduced by 63.6% and 51.2%, respectively, compared with ones of the traditional linear loading methods. Further research based on XFEM shows that the initial crack depth is between 0.25mm and 0.4mm, and the cracking angle and the crack offset distance can also meet the precision cropping requirement, which provides a technical guarantee for truly improving the cropping quality.